Icelandic journalists in a changing media system: Emphasizing classic journalistic roles but under increasing pressure - Guðmundsson, Birgir; Ólafsson, Jón Gunnar; Jóhannsdóttir, Valgerður (Stofnun stjórnmála og stjórnsýslu, 2024)
In this article we examine changes in role perceptions of Icelandic journalists and the pressure they perceive on their daily work. The media environment in Iceland has gone through drastic changes in recent years which has, as in other countries, altered the way news is produced, distributed, received, and the overall role the news media plays in society. Increasing competition for peoples’ attention, the impact of the internet, social media and powerful tech giants, have among other things resulted in financial difficulties in the media market, bankruptcy and layoffs. The purpose of the research presented here is to examine if and how these changes have affected journalists’ views about their role in society and if they perceive increased pressure on their work. We present data from the international comparative Worlds of Journalism Study (WJS) in Iceland from 2021 (n=239). The new data is both quantitative and qualitative, i.e., a survey among the news journalism population in the country and qualitative in-depth interviews with 30 journalists. The findings are compared to the results from WJS in 2012. Our results indicate that Icelandic journalists place greater emphasis now than a decade earlier on classic journalistic roles, such as being a detached observer and scrutinizing those in power. At the same time, they report encountering more external interference and pressure in their work, especially journalists working for private media outlets but to a lesser extent those in the Public Service Media. Í þessari grein er fjallað um rannsókn á viðhorfum íslenskra blaðamanna til hlutverks síns í samfélaginu og upplifun þeirra af utanaðkomandi þrýstingi á störf sín. Fjölmiðlaumhverfið á Íslandi hefur gengið í gegnum miklar breytingar á undanförnum árum sem hafa, eins og í öðrum löndum, breytt því hvernig fréttir eru búnar til, þeim dreift og hvernig lesendur nálgast fréttir og jafnframt vakið spurningar um hlutverk fjölmiðla. Vaxandi samkeppni um athygli fólks, áhrif netsins, samfélagsmiðla og áhrifamikilla ...